+0  
 
0
79
1
avatar

The quadratic ax^2 + bx + c can be expressed in the form 2(x - 8)^2 + 4. When the quadratic 3ax^2 + 3bx + 3c is expressed in the form n(x - h)^2 + k, what is h?

 May 1, 2021
 #1
avatar+121000 
+2

2(x - 8)^2  +  4       (expand)

 

2 (x^2  - 16x + 64)  +  4  =

 

2x^2  - 32x  +  128 + 4  =

 

2x^2  - 32x  +  132         a  =  2       b  = -32        c   =  132

 

So

 

3(2)x^2   + 3(-32)x + 3 (132)   =

 

3  ( 4x^2  - 32x  + 132)  =       (factor out 4)

 

3 * 4  ( x^2  - 8x + 33)   =

 

12   [ x^2  - 8x  +  16  +  17 ]   =         (factor x^2 - 8x + 16)

 

12 [ ( x - 4)^2  +  17 ]  =                     (distribute  the 12  across the terms in the brackets )

 

12 (x - 4)^2  +  204

 

h =  4

 

cool cool cool

 May 1, 2021

12 Online Users